SnS Nanoflakes/Graphene Hybrid: Towards Broadband Spectral Response and Fast Photoresponse - Xiangyang Li; Shuangchen Ruan; Haiou Zhu (Nanomaterials, 2022)
High responsivity has been recently achieved in a graphene-based hybrid photogating mechanism photodetector using two-dimensional (2D) semiconductor nanosheets or quantum dots (QDs) sensitizers. However, there is a major challenge of obtaining photodetectors of fast photoresponse time and broad spectral photoresponse at room temperature due to the high trap density generated at the interface of nanostructure/graphene or the large band gap of QDs. The van der Waals interfacial coupling in small bandgap 2D/graphene heterostructures has enabled broadband photodetection. However, most of the photocarriers in the hybrid structure originate from the photoconductive effect, and it is still a challenge to achieve fast photodetection. Here, we directly grow SnS nanoflakes on graphene by the physical vapor deposition (PVD) method, which can avoid contamination between SnS absorbing layer and graphene and also ensures the high quality and low trap density of SnS. The results demonstrate the extended broad-spectrum photoresponse of the photodetector over a wide spectral range from 375 nm to 1550 nm. The broadband photodetecting mechanisms based on a photogating effect induced by the transferring of photo-induced carrier and photo-hot carrier are discussed in detail. More interestingly, the device also exhibits a large photoresponsivity of 41.3 AW−1 and a fast response time of around 19 ms at 1550 nm. This study reveals strategies for broadband response and sensitive photodetectors with SnS nanoflakes/graphene.